The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20964/2017.11.86
|View full text |Cite
|
Sign up to set email alerts
|

Failure Pressure Estimations for Pipes with Combined Corrosion Defects on the External Surface: A Comparative Study

Abstract: In this research paper, the failure pressure predictions were obtained for a pipeline section by analyzing a combined corrosion defects, which joins together a general corrosion and a pitting corrosion defects. Well-known conventional mathematical methods were used in this study to predict the failure pressure of corroded steel pipelines, such as: B31G, RSTRENG-1, Shell-92, DNV, PCORR, and Fitnet FFS. The equations reported for corrosion defects with more complex characteristics developed by Choi et al., and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Their results illustrate that i) the failure pressure increases for higher metal grades, and ii) the relative error with the FEM simulation increases as defect depth growths, obtaining closer matching for the DNV approach. Terán et al [23] compared the ASME B31G, RSTRENG, SHELL92, DNV, PCORRC, Fitnet FFS, Choi's model and CPS criteria based on FEM simulations in an API 5L X52 steel pipe with a diameter of 609.6 mm. For this purpose, they implemented the Von Mises criterion in nine simulations with semi-elliptical pits associated with a combined metal loss: uniform (50%) and localized (50%) corrosion defects.…”
Section: Prediction Error Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results illustrate that i) the failure pressure increases for higher metal grades, and ii) the relative error with the FEM simulation increases as defect depth growths, obtaining closer matching for the DNV approach. Terán et al [23] compared the ASME B31G, RSTRENG, SHELL92, DNV, PCORRC, Fitnet FFS, Choi's model and CPS criteria based on FEM simulations in an API 5L X52 steel pipe with a diameter of 609.6 mm. For this purpose, they implemented the Von Mises criterion in nine simulations with semi-elliptical pits associated with a combined metal loss: uniform (50%) and localized (50%) corrosion defects.…”
Section: Prediction Error Comparisonmentioning
confidence: 99%
“…There are other relevant approaches that were already discussed such as Choi et al [51], Ma et al [81], and Netto et al [16]. Other comparisons using FEM are summarized in [23].…”
Section: Prediction Error Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…it was shown that numerical simulation with CDM could be used to carry on "virtual experiments" for the determination of the material fracture toughness with high degree of accuracy. Using conventional mathematical methods, B31G, RSTRENG-1, Shell-92, DNV, PCORR, and Fitnet FFS, Terán et al [6] analyzed a combined corrosion defects, which joins together a general corrosion and a pitting corrosion defects to predict the failure pressure of corroded steel pipelines. It was found that the failure pressure predictions of general corrosion combined with a pit are affected by the length and depth of two corrosion defects.…”
Section: Introductionmentioning
confidence: 99%
“…The shape defects, which are characterised by large plastic deformations with (or without) reduced wall thickness, are very dangerous because they can initiate (or can be combined with) various types of corrosion defects or cracks [20][21][22][23]. Therefore, these defects should also be examined to decide whether the pipelines of this age can be safely used further, or whether these defects must be removed.…”
Section: Introductionmentioning
confidence: 99%